Mitigating Furniture Supply Chain Risks: A House of Risk Approach: Mengurangi Risiko Rantai Pasokan Mebel: Pendekatan Rumah Risiko - Mutiara Rahmi; Dira Ernawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background The furniture manufacturing industry relies on complex production processes and natural raw materials, creating vulnerability to supply chain disruptions that threaten production continuity. Specific Background PT XYZ, a furniture manufacturer in East Java, experiences recurring problems in its upstream supply chain, particularly delays, material inconsistencies, and operational disruptions related to wood-based raw materials used in table production. Knowledge Gap Previous studies on furniture supply chains have largely applied general risk management approaches, while structured and quantitative applications of the House of Risk method in upstream furniture supply chains remain limited. Aims This study aims to identify critical supply chain risks, prioritize dominant risk agents, and formulate mitigation strategies using the House of Risk framework. Results The analysis identifies 21 risk events and 26 risk agents, with 11 dominant risk agents accounting for more than 80% of aggregate risk potential, primarily related to human error, material variability, storage conditions, coordination issues, and incomplete drying of wood. Novelty This study demonstrates the structured application of the House of Risk method in the upstream segment of the furniture supply chain, an area that has received limited empirical attention. Implications The findings provide practical guidance for furniture manufacturers to strengthen supply chain resilience through targeted mitigation strategies such as training, standardization, digital coordination, and material quality control, while also contributing empirical evidence to supply chain risk management literature. Highlights: Dominant supply chain vulnerabilities originate from human error, raw material variability, and storage conditions. A small group of risk agents accounts for the majority of upstream supply chain disruptions. Structured mitigation prioritization supports systematic risk handling in furniture manufacturing operations. Keywords: House of Risk, Supply Chain Risk, Furniture Manufacturing, Risk Mitigation, Upstream Supply Chain